Worker health impacts from working from home during the COVID-19 pandemic. - de Oliveira, Thais Cristine dos Santos; Muzeka, Ana Luiza Pedrini; Batista, Emilly; dos Santos, Gessica Nair Farias Eleuterio; Rocha, Luiz Fernando Isaias da; Legey, Ângela Luiza Cunha; Klein, Alison Alfred; Motter, Arlete Ana (Work, 2022)
BACKGROUND: COVID-19 was first reported in December 2019 in Wuhan, China. With the rapid spread of the virus, the World Health Organization (WHO) in March 2020 declared the initial outbreak of the disease a pandemic. OBJECTIVE: To assess the challenges and consequences of working from home on worker health during the COVID-19 pandemic. METHOD: Cross-sectional and descriptive study developed in Curitiba, Paraná, Brazil, from December 2020 to January 2021. An online questionnaire was used to interview workers working from home and later a statistical analysis was performed. RESULTS: 327 workers from various fields of activity participated, mainly those from the south of the country, women, and workers who develop activities in education. In addition, results show anxiety and/or irritability, weight gain, discouragement, headaches and muscle and joint problems. CONCLUSION: Most participants found an increase in working hours while working from home, with several breaks during the day and adequate furniture. However, there was a worsening of physical pain and changes in symptoms of anxiety, weight gain, discouragement and headaches.